PENGATURAN TINDAK PIDANA KORUPSI SEBELUM DAN SESUDAH BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KUHP, DALAM UPAYA MENURUNKAN ANGKA KORUPSI PADA SEKTOR SWASTA - Zulfiani, Anita; Probohudono, Agung Nur; Sangka, Khresna Bayu (Universitas Ekasakti, 2023)
Corruption is a legal issue that always comes up. The level of corruption in the private sector is quite high. Based on Corruption Eradication Commission (KPK) data, in 2004-2021, private parties who were convicted of corruption reached 359 people or 26%. This paper discusses the regulation regarding corruption, especially related to the private sector, before and after the enactment of Law Number 1 of 2023 concerning the Criminal Code. This paper uses normative writing methods with statutory and comparative approaches. Corruption is regulated in the Criminal Code Articles 209, 210, 378, 388, 418, 419, and Article 420. These articles were revoked after the enactment of Corruption Law. Corruption regulation in Law Number 1 of 2023 concerning the Criminal Code are contained in Articles 603, 604, 605(1), and Article 606 (1). There have been changes in the regulation of corruption, including the abolition of the threat of the death penalty. The criminal act of corruption in the New Criminal Code does not make corruption cases lose its category as a special crime and extraordinary crime, because the existence of corruption articles in the New Criminal Code aims to compile a codification of criminal law, where corruption articles are generally formulated as core crimes, which function as bridging articles between the New Criminal Code and laws outside the New Criminal Code. The corruption law as a lex specialis requires a lex generalis in criminal code, this codification does not eliminate corruption from it’s characteristic as a special crime, and the Corruption Law in general is still in force, as well as the KPK (Corruption Eradication Commission) is still authorized to deal with corruption.